2021
DOI: 10.1101/2021.05.11.443637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical ripples during NREM sleep and waking in humans

Abstract: Hippocampal ripples index the reconstruction of spatiotemporal neuronal firing patterns essential for the consolidation of memories in the cortex during non-rapid eye movement (NREM) sleep. However, it is not known whether ripples are generated in the human cortex during sleep. Here, using human intracranial recordings, we show that ~70ms long ~80Hz ripples are ubiquitous in all regions of the cortex during NREM sleep as well as waking. During waking, cortical ripples occur on local high frequency activity pea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 87 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…( 19 ) was the first to describe cortical high-frequency events (cortical ripples). They observed these events in default-mode network regions (prefrontal and retrosplenial cortex), as well as the PPC, and they tended to occur together with HPC-R. Later, these oscillations were also reported in human subjects ( 27 31 ). It was also shown that these co-occurring events became more common after learning ( 19 ).…”
Section: Discussionmentioning
confidence: 89%
“…( 19 ) was the first to describe cortical high-frequency events (cortical ripples). They observed these events in default-mode network regions (prefrontal and retrosplenial cortex), as well as the PPC, and they tended to occur together with HPC-R. Later, these oscillations were also reported in human subjects ( 27 31 ). It was also shown that these co-occurring events became more common after learning ( 19 ).…”
Section: Discussionmentioning
confidence: 89%
“…However, thalamocortical connections are also very rare compared to cortico-cortical ( 36 ). Given the strong relationship of cortical ripples to upstates, and less strongly to sleep spindles ( 11 ), and the role of thalamocortical interactions in the generation of upstates and spindles ( 37 ), it is possible that thalamocortical modulation via sleep waves may contribute to cortico-cortical ripple synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported, using human intracranial recordings, that ∼70-ms-long, ∼90-Hz ripples are ubiquitous in all regions of the cortex during NREM as well as waking ( 11 ). During waking, cortical ripples occur on local high-frequency activity peaks.…”
mentioning
confidence: 99%